MATERIAL AND ENERGY FLOW MANAGEMENT- LIFELONG LEARNING COURSES EXPERIENCES - Zoltan Zavargo; Aleksandar Jokić; Jelena Pavličević; Bojana Ikonić; Oskar Bera (Journal of Engineering & Processing Management, 2016)
Material and energy flow management is among the most important factors for the economicgrowth of a society in harmony with nature and it will play the main role only in the area ofsustainable development. The three lifelong learning courses were developed in order to introducethis concept to the industry professionals and administration at the city and regional level. Themain goal was to heighten awareness of participants to this topic, as in Serbia it is relatively newapproach in corporate and administrative management. The results of the courses confirmed theinterest in this kind of lifelong learning courses with suggestion to join it in a single course withemphasise on the specific participant’s problems.
Keywords: lifelong learning; material and energy flow management